ANALISIS USAHATANI PEMBESARAN IKAN PADA KERAMBA JARING APUNG (KJA) DAN KOLAM DI KOTA JAMBI - Rosyani; Pritychia, Velly Fika; Hamid, Ernawati (JALOW | Journal of Agribusiness and Local Wisdom, 2020)
This study aims to determine; 1) This study aims to determine; 1) To find out the description of nila and patin farming in floating net cages (KJA) and ponds in Jambi City, 2) To find out how much the level of production, cost and income of nila and patin farming in floating net cage media (KJA) and pond, 3) To analyze the income comparison of nila and patin farming in floating net cages (KJA) and ponds. The results showed that the average income received by nila farmers in KJA was Rp. 4,782,000, - and nila in a pond of Rp. 4,228,200, - while the average acceptance of patin at KJA is Rp. 6,487,000, - and patin in the pool of Rp. 7,137,000, - The average income of nila in KJA is Rp. 596,747, - and Rp. 129,300, - nila income in the pond, while patin in KJA is Rp. 98,207, - and Rp. 404,007, - in the pond. Analysis of t-test on nila with thit = 3.485> t Table (Î±2 = 5% df = 18 (2,100)) which means Ha is rejected, then farming income of nila in KJA is greater than pond, while patin value is thit = -4,435> t Table = 2,100, which means Ha is accepted, then significantly the income of catfish farming is similar or smaller than in ponds